Formulation Optimization and Quality Analysis of Dendrobium officinale Chewable Tablets - Wenyu ZHANG; Xianshu FU; Xue BAI; Shiwen WU; Jiabin LI; Xiaoping YU; Mingzhou ZHANG; Zihong YE (Shipin gongye ke-ji)
To explore whether Dendrobium officinale, Polygonatum sibiricum, and Ziziphus jujuba can be used as active pharmaceutical ingredient (APIs), a functional snack that is easy to carry and eat was developed. In this study, the design of experiment (DOE) scheme was used to determine the optimal ratio of D. officinale, P. sibiricum, and Z. jujuba based on the measured mass fractions of polysaccharides, flavonoids, and polyphenols in the drug. A single-factor experiment was used to study the effects of excipients on the appearance, taste, hardness, and weight difference of chewable tablets, and the optimal formula was selected by combining the response surface optimization and multi-index weight methods. Results showed that the optimal compound ratio of the main ingredients of D. officinale chewable tablets (mass fraction) was D. officinale:P. sibiricum:Z. jujuba=35%:10%:5%, and the corresponding total mass fractions of polysaccharides, flavonoids, and polyphenols were 159.64±0.14, 79.44±0.35, and 78.10±0.28 mg/g, respectively. The mass fraction ratios of erythritol, mannitol, and whey protein in the excipient fractions were 13%, 13%, and 6%, respectively. The differences in appearance, taste, hardness, and weight of D. officinale chewable tablets under the optimal formula were 7.80±0.63 points, 7.80±0.42 points, 23.72±0.15 N, and 2.57%±0.13%, respectively. The comprehensive score was 21.87±0.83 points. Results of physical property evaluation and the dissolution test of D. officinale chewable tablets showed that the water content, adhesion, elasticity, and chewiness were 2.23%±0.92%, 12.75±0.54 mJ, 7.08±0.58 mm, and 0.41±0.67 mJ, respectively, and the cumulative dissolution reached 79.80%±0.75% at 60 min. Chewable tablets made from D. officinale, P. sibiricum, and Z. jujuba have a high active ingredient content, good sensory evaluation, and easy dissolution.